2016
DOI: 10.1002/anie.201609837
|View full text |Cite
|
Sign up to set email alerts
|

Copper Catalysis in Living Systems and In Situ Drug Synthesis

Abstract: The copper-catalyzed azide-alkyne cycloaddition (CuAAC) reaction has proven to be a pivotal advance in chemical ligation strategies with applications ranging from polymer fabrication to bioconjugation. However, application in vivo has been limited by the inherent toxicity of the copper catalyst. Herein, we report the application of heterogeneous copper catalysts in azide-alkyne cycloaddition processes in biological systems ranging from cells to zebrafish, with reactions spanning from fluorophore activation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
130
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(134 citation statements)
references
References 48 publications
0
130
0
Order By: Relevance
“…Current examples of metal‐catalyzed reactions in biological settings (Table ) include ruthenium‐mediated uncaging of allyl carbamates and protein labeling, iron‐mediated uncaging of azide groups, palladium‐mediated uncaging of allenyl, propargyloxycarbonyl, and allyl carbamate groups, as well as palladium‐mediated N‐dealkylation, Suzuki–Miyaura, and Sonogashira cross‐couplings, and gold‐mediated hydroarylative cyclizations . In addition, in vivo cell‐based examples of copper‐catalyzed azide–alkyne cycloaddition and palladium‐mediated carbon monoxide triggered carbonylation also exist …”
Section: Metal Complex Catalysis Within Biological Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current examples of metal‐catalyzed reactions in biological settings (Table ) include ruthenium‐mediated uncaging of allyl carbamates and protein labeling, iron‐mediated uncaging of azide groups, palladium‐mediated uncaging of allenyl, propargyloxycarbonyl, and allyl carbamate groups, as well as palladium‐mediated N‐dealkylation, Suzuki–Miyaura, and Sonogashira cross‐couplings, and gold‐mediated hydroarylative cyclizations . In addition, in vivo cell‐based examples of copper‐catalyzed azide–alkyne cycloaddition and palladium‐mediated carbon monoxide triggered carbonylation also exist …”
Section: Metal Complex Catalysis Within Biological Systemsmentioning
confidence: 99%
“…Although pioneering studies have been reported in this field, it has been largely limited to either cell or bacterial systems, the only exception being two studies where metal resins were directly injected into the embryo yolks of zebrafish . In order for metal complex catalysts to become therapeutically applicable, one major obstacle that has to be addressed is how to localize metal complexes to specific diseased organs or tumors before they are metabolized and excreted.…”
Section: Metal Complex Catalysis Within Biological Systemsmentioning
confidence: 99%
“…[9] In fact, the active drugs may have totally different properties at different sites in living cells.Mitochondria are important targets of many drugs owing to their critical roles in maintaining cellular survival and function. [13] Bradley and co-workers designed aheterogeneous copper catalyst to synthesize an anticancer agent. [11] To solve the problems associated with drug delivery,the concept of "click to release" for drug synthesis and delivery has been put forward.…”
mentioning
confidence: 99%
“…In contrast, through the CuAACr eaction, the simplest terminal alkyne and azide could enable the synthesis of ad esired compound or drug, thus avoiding complex presynthesis.T his "bottom-up" model for drug synthesis is more suitable for av ariety of drugs.H owever,s ite-specific CuAACfor localized drug synthesis in living cells is still in its infancy. [13] Bradley and co-workers designed aheterogeneous copper catalyst to synthesize an anticancer agent. However, the size of their resin beads catalyst was around 150 mm, and thus much larger than cells.T herefore,the catalyst could not be endocytosed by living cells,and the reactions were carried out in the extracellular matrix.…”
mentioning
confidence: 99%